Recent trends in extraction, purification, structural characterization, and biological activities evaluation of Perilla frutescens (L.) Britton polysaccharide - Zhu, Ling; Guan, Lijun; Wang, Kunlun; Ren, Chuanying; Gao, Yang; Li, Jialei; Yan, Song; Zhang, Xindi; Yao, Xinmiao; Zhou, Ye; Li, Bo; Lu, Shuwen (Frontiers in Nutrition, 2024)
Perilla frutescens (L.) Britton is an annual herb plant of the Perilla genus in the Labiatae family, which is commonly utilized as an edible and medicinal resource. Polysaccharides are among the major components and essential bioactive compounds of P. frutescens, which exhibit a multitude of biological activities, including antioxidant, antitumor, anti-fatigue, immunoregulation, hepatoprotective, anti-inflammatory, and lipid-lowering effects. As a natural carbohydrate, P. frutescens polysaccharide has the potential to be utilized in the development of drugs and functional materials. In this paper, we provide an overview of progress made on the extraction, purification, structural characterization, and bioactivity of polysaccharides from different parts of P. frutescens. The challenges and opportunities for research are